Childhood obesity and bone metabolism: another problem to deal with - Mennini, Maurizio; Mosca, Antonella (Progress in Nutrition, 2014)
The problem of childhood obesity is becoming a worrying epidemiological volume and the age of onset seems to be constantly anticipated. Therefore, these pediatric patients are often faced with complications typical of the adult. In a recent article by Wang JW et al. (1), the authors conclude that body composition is related to serum osteocalcin levels in overweight and obese children. We really appreciated their attempt to deal with a controversial and not yet clarified issue in an original way. However, we believe that their findings can be discussed in the light of recent evidence. We emphasize that the correlation between BMI and risk of fracture appears to be extremely controversial. We first need to better define the real influence of nutritional status on bone metabolism and then defining the biochemical mechanisms of mutual influence. Certainly, the need for childhood obesity prevention campaigns is compelling.